Formulasi dan Uji Antibakteri Sediaan Pasta Gigi Ekstrak Parijoto (Medinilla Speciosa) dengan Eggshell Hydroxyapatite (EHA) - Zaki Syariifuddin Taqiy; Teguh Imanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Dental caries is one of the dental and oral health problems related to the activity of bacteria such as Streptococcus mutans and Staphylococcus aureus. The use of fluoride as an active ingredient in toothpaste has several limitations, so the development of natural-based alternative ingredients is one approach that needs to be studied. This study aims to formulate and evaluate the physical stability and antibacterial activity of a toothpaste preparation combining parijoto fruit extract (Medinilla speciosa) and Eggshell Hydroxyapatite (EHA). The study was conducted experimentally using four formulas, namely F0 (without parijoto extract), F1 (10% parijoto extract), F2 (12.5% ​​parijoto extract), and F3 (15% parijoto extract). Evaluation of the preparation includes organoleptic tests, phytochemical screening, homogeneity, pH, viscosity, foam height, and antibacterial activity tests using the well diffusion method against S. aureus and S. mutans bacteria. The results of phytochemical screening showed that parijoto fruit extract contains phenolic compounds, flavonoids, saponins, and tannins. The results of the viscosity test in F0, F1, F2, and F3 were 14070 cps ± 809.03, 46600 cps ± 866.54, 43090 cps ± 3136.61, and 41910 cps ± 2200.27, respectively. Variations in extract concentration significantly affect viscosity with viscosity statistics results (p <0.05). pH test results F0: 7.87 ± 0.5918, F1: 7.44 ± 0.3241, F2: 7.33 ± 0.4082, F3: 7.40 ± 0.1625, Foam height F0: 1.56 cm ± 0.40415, F1: 2.06 cm ± 0.05774, F2: 2.13 cm ± 0.11547, F3: 1.93 cm ± 0.11547. The results of the antibacterial test of Staphylococcus aureus showed an inhibitory value of F0 (negative control) of 1.66 cm ± 0.24664, positive control 1.63 cm ± 0.14433, F1 (10% extract) 1.60 cm ± 0.08660, F2 (12.5% ​​extract) 1.83 cm ± 0.32145, F3 (15% extract) 1.70 cm ± 0.05. The comparison between groups did not have a significant value (p > 0.05). The results of the antibacterial test of Streptococcus mutans F0 (negative control) 1.53 cm ± 0.02886, positive control 1.66 cm ± 0.24664, F1 (10% extract) 1.45 cm ± 0.05, F2 (12.5% ​​extract) 1.48 cm ± 0.10408, F3 (15% extract) 1.50 cm ± 0.05. The comparison between groups was not significant (p>0.05). Based on the results of the study, the combination of parijoto fruit extract and EHA can be formulated into a toothpaste preparation with good physical characteristics, but increasing the concentration of parijoto extract has not shown a significant effect on antibacterial activity compared to the control formula.